Hydrogels: Robust Mechanochromic Elastic One‐Dimensional Photonic Hydrogels for Touch Sensing and Flexible Displays (Advanced Optical Materials 7/2014). Issue 7 (15th July 2014) - Wang, Xiao‐Qiao; Wang, Cai‐Feng; Zhou, Zhen‐Fang; Chen, Su
<x xml:space="preserve">Abstract</x> On page 652, S. Chen and co‐workers exploit a magnetic assembly technique for the fabrication of mechanochromic hydrogels sensitive in a low pressure regime. These photonic materials, made from 1D arrays of Fe3O4 nanoparticles immobilized in elastic hydrogels, show reversible wide color variation within 1 s through a compression‐decompression process. Slight touches on the hydrogels, with pressures down to 1 kPa, can induce visual color changes, suggesting an alternative for flexible touch sensors and displays. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>